Governing Africa’s Seas in the Neoliberal Era. - (:unkn) unknown (My University, 2019)
The governance of the seas has profoundly changed in the 21st century with the explosion of maritime transport, the globalization of the exploitation of marine resources, and the growing concern for environmental issues. The idea of an integrated policy of seas and oceans management became a cornerstone of international and national instruments aiming to regulate maritime circulation and exploitation of marine resources. Integrated maritime management policies put emphasis on liberalization of the marine sectors and resources and the security agenda, taken in its broad sense to guarantee freedom of trade and environmental sustainability. These efforts, whose putative purpose is to combine economic, social and environmental goals, has resulted in an unsteady balance between different sectors, scales and actors and let the door open to controversies, dissent and politics. Although the priorities of this global policy agenda continue to transform the maritime governance in Africa, the African states and societies are also actively reshaping it. While African states alter international maritime policies according to their own ends, these are also constantly molded through struggles over norms, resources and spaces and, conflicts arising from the dialectics of possession and dispossession.
Keywords: African Research